Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan pada Perusahaan Manufaktur di BEI Tahun 2017-2020 - Putri Bunga Leani; Desy Nur Pratiwi; Wikan Budi Utami (Nur Science Institute, 2022)
This study aims to determine the significance of the effect of managerial ownership, institutional ownership, independent ownership, and audit committee on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018–2020. The type of data in this study is secondary data (quantitative). The total population in this study was 201 companies in the consumer goods industry for the period 2018-2020. The number of samples used in this study were 55 companies, using purposive sampling method and multiple regression linear data analysis. Data were processed using SPSS 23. Simultaneous test results show that managerial ownership, institutional ownership, independent ownership, and audit committee have a significant effect on the company's financial performance. The results of the partial test show that only the independent ownership variable has a significant effect on the company's financial performance, while managerial ownership, institutional ownership, and the audit committee have no significant effect on the company's financial performance.